ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Bank Umum Go Public yang terdaftar di Bursa Efek Indonesia Tahun 2012 – 2016) - Asriyani, Rahma; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to analyze the factors that effects firm’s value with profitability as the intervening variable on Go Public commercial bank listed on the Indonesian Stock Exchange (IDX) in the 2012-2016 period. Price Book Value (PBV) is the dependent variable in this study. There are four independent variables used, they are Based Lending Rate (BLR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operational Expense to Operational Income (BOPO), and Return on Asset (ROA) as the intervening variable.The population used in this study consisted of go public commercial banks listed on IDX in the 2012-2016 period, bringing the total population is consist of 31 companies. The total samples are 19 companies. The data analysis methods which are used is path analysis which are the development of linear regression analysis and used the Sobel Test to analyze the mediation effect of the intervening variable.The result of this study shows that BLR, NPL, LDR has insignificant effect to ROA, BOPO has significant negative effect to ROA. BLR, LDR, ROA has significant effect to PBV. NPL and BOPO has insignificant effect to PBV. ROA can’t mediate the effect of BLR, NPL, LDR, and BOPO to PBV.